2000
DOI: 10.1017/s1355838200992264
|View full text |Cite
|
Sign up to set email alerts
|

A four-nucleotide translation enhancer in the 3′-terminal consensus sequence of the nonpolyadenylated mRNAs of rotavirus

Abstract: The 59 cap and poly(A) tail of eukaryotic mRNAs work synergistically to enhance translation through a process that requires interaction of the cap-associated eukaryotic initiation factor, eIF-4G, and the poly (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
3
38
0
1
Order By: Relevance
“…RV mRNAs are unique in that they possess a 5Ј cap structure but lack 3Ј poly(A) tails (26,27), and several studies have revealed the importance of these structures for efficient genome replication and translation (28)(29)(30). In this study, each of the authentic 5Ј and 3Ј end structures were planned to be obtained with vaccinia virus-encoded capping enzyme and the HDV ribozyme sequences inserted in the transcription plasmids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RV mRNAs are unique in that they possess a 5Ј cap structure but lack 3Ј poly(A) tails (26,27), and several studies have revealed the importance of these structures for efficient genome replication and translation (28)(29)(30). In this study, each of the authentic 5Ј and 3Ј end structures were planned to be obtained with vaccinia virus-encoded capping enzyme and the HDV ribozyme sequences inserted in the transcription plasmids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that RbcS mRNAs encode photosynthetic proteins that accumulate to very high levels in the chloroplasts of C 4 as well as C 3 plants (Edwards and Huber, 1981;Miziorko and Lorimer, 1983;Sage et al, 1987), it might be expected that these transcripts would contain sequences capable of acting as strong translational enhancers. Translational enhancement is primarily known from some plant and animal viral RNAs (Gallie, 1993(Gallie, , 2002De La Luna et al, 1995;Chizhikov and Patton, 2000;Salvatore et al, 2002). There are also several examples of plant cellular transcripts showing enhanced translation capabilities (Pitto et al, 1992;Gallie and Young, 1994;Bate et al, 1996;Ling et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…RNA viruses that lack a cap and/or a poly(A) tail have developed alternative strategies for translation regulation involving the 3Ј UTR (9,22). The roles of the 3Ј UTR in translational enhancement of viral RNAs have been studied with human and animal viral systems, including HCV (13) and rotavirus (4). Translation enhancer elements within the 3Ј UTRs of plant viruses that lack both the cap and the poly(A) tail have been implicated as determinants for translation efficiency in tomato bushy stunt virus (46), satellite necrosis virus (22), BYDV (1,40), and TCV (29).…”
Section: Discussionmentioning
confidence: 99%